Bricklaying Robot Lifting and Levelling System - Piotr Wos; Ryszard Dindorf; Jakub Takosoglu (Communications - Scientific letters of the University of Zilina, 2021)
The article presents the concept of building and controlling a Bricklaying Robotic System (BRS). The research presents the design process and how to control a four-cylinder electro-hydraulic servo drive system. The article presents a mathematical model and optimizes the process of aligning the mobile support platform of the masonry robot. The lifting mechanism was presented and its kinematic analysis performed. The mathematical model of the hydraulic system was described. The control system, designed for the masonry robot lifting platform, includes position errors for a single drive axis and synchronization errors between the axes.